Effectiveness of influenza and pneumococcal polysaccharide vaccines against influenza-related outcomes including pneumonia and acute exacerbation of cardiopulmonary diseases: Analysis by dominant viral subtype and vaccine matching - Song, Joon Young (PLoS One, 2018)
BACKGROUND: Influenza and pneumonia are leading causes of morbidity and mortality among the elderly. Although vaccination is a main strategy to prevent these infectious diseases, concerns remain with respect to vaccine effectiveness. METHODS: During three influenza seasons (2014–2015, 2015–2016 and 2016–2017), we evaluated the effectiveness of the influenza and pneumococcal vaccines against pneumonia and acute exacerbation of cardiopulmonary diseases among the elderly aged ≥65 years with influenza-like illness (ILI). Demographic and clinical data were collected prospectively. RESULTS: Among 2,119 enrolled cases, 1,302 (61.4%) and 871 (41.1%) received the influenza vaccine and 23-valent pneumococcal polysaccharide vaccine (PPV23), respectively. During an A/H3N2-dominant season with poor influenza vaccine effectiveness (2014–2015 season), neither the influenza vaccine nor PPV23 showed significant effectiveness against pneumonia or acute exacerbation of cardiopulmonary diseases. During seasons with good influenza vaccine effectiveness (2015–2016 and 2016–2017 seasons), the influenza vaccine was effective in preventing pneumonia, but PPV23 was not. In particular, the influenza vaccine was effective in preventing acute exacerbation of heart diseases (75.0%) during the A/H1N1-dominant 2015–2016 season. CONCLUSION: The influenza vaccine was effective in preventing pneumonia only during vaccine-matched seasons with good effectiveness against circulating influenza viruses. In addition, the influenza vaccine was cardio-protective during a vaccine-matched A/H1N1-dominant season.